An electromechanical, patient positioning system for head and neck radiotherapy. (5th September 2017) - Ostyn, Mark; Dwyer, Thomas; Miller, Matthew; King, Paden; Sacks, Rachel; Cruikshank, Ross; Rosario, Melvin; Martinez, Daniel; Kim, Siyong; Yeo, Woon-Hong
Abstract: In cancer treatment with radiation, accurate patient setup is critical for proper dose delivery. Improper arrangement can lead to disease recurrence, permanent organ damage, or lack of disease control. While current immobilization equipment often helps for patient positioning, manual adjustment is required, involving iterative, time-consuming steps. Here, we present an electromechanical robotic system for improving patient setup in radiotherapy, specifically targeting head and neck cancer. This positioning system offers six degrees of freedom for a variety of applications in radiation oncology. An analytical calculation of inverse kinematics serves as fundamental criteria to design the system. Computational mechanical modeling and experimental study of radiotherapy compatibility and x-ray-based imaging demonstrates the device feasibility and reliability to be used in radiotherapy. An absolute positioning accuracy test in a clinical treatment room supports the clinical feasibility of the system.